The state of consciousness: From perceptual alterations to dissociative forms. Analysis of neurobiological and clinical profiles - Giulio Perrotta (Journal of Neurology, Neurological Science and Disorders - Peertechz Publications, 2021)
Consciousness, understood as the state of vigilance of the mind or the state of being conscious and present with respect to ourselves and the surrounding environment, allows us to interact at every level, unless there is a precise cause capable of interfering with and altering the functional state of our consciousness. This paper investigates the main hypotheses of alteration, up to the most dysfunctional and pathological forms of psychotic pictures.